Relación entre el control interno y la gestión de compras en la Municipalidad Distrital de Punchana periodo 2024 - Vela Tipa, Erika Juliana (2025)
This research analyzes the relationship between internal control and procurement management in the District Municipality of Punchana during 2024, using a quantitative correlational approach and a non-experimental design. The study is based on the general hypothesis that the implementation of robust internal controls positively influences procurement processes, contributing to improved efficiency, transparency, and appropriate use of public resources. To verify this relationship, the Spearman correlation coefficient was applied, using data collected through questionnaires administered to a sample of 159 employees involved in procurement management. The results show a significant positive correlation between internal control and procurement management, validating the main hypothesis. Additionally, positive relationships were identified between internal communication and supplier service levels, risk assessment and procurement procedures, and internal auditing with the rotation of accounts payable. These findings reinforce the importance of internal control in public administration, emphasizing the need to strengthen auditing, risk management, and communication to optimize procurement processes. In conclusion, this research provides relevant empirical evidence to promote continuous improvements in public management and administrative efficiency within the municipality.